Mediatisations of Emotions in Theory: The Media Studies Perspective - Duda, Aneta (Roczniki Kulturoznawcze, 2023)
This article provides a synthetic review of key theoretical approaches adopted by media experts in their studies: psychoanalytic, psychobiological, philosophical approaches and critical perspective of media cultural studies. An attempt is made to systematize the major research areas of media representations of emotions. The analysed emotions are treated as a predictor of the choice of media broadcast, an element of media exposition, a determinant of psychological and behavioural effects of media message, an affective reaction to exposition, and a “culture of emotions”. A synthesis of the conditions and contexts behind the emotions presented in the media. Groups of determinants and affective contexts for media situations were defined as: media types, co-recipients of the message, the role of witness/observer, the level of identification, forms and means of emotion channelling, media competence.